Quasi resonant soft switching high gain interleaved quadratic coupled inductor converter - Liang Chen; Desheng Rong; Xuanjin Sun (Scientific Reports)
Abstract This paper conducts topology transformation based on the Buck/Boost converter. The front-end unit adopts an interleaved structure and passive clamp branches to enhance voltage transformation capability. This setup ensures a smoother input inductor current, mitigating current ripple and improving overall converter performance. At the same time, a dual-coupling structure is introduced, and a voltage multiplier cell is formed by using the secondary side of the dual-coupled inductor connected in series with the diode-capacitor (D-C) branch. It can once again enhance the voltage and suppress the impact force, use generalized quasi-resonance to achieve the zero-current-switching (ZCS) of the loop, and reduce the voltage stress of the devices. An interleaved quadratic Boost converter is proposed, a detailed theoretical analysis of its working principle and performance characteristics is carried out, and various indicators are compared horizontally in different converters. To validate the theoretical framework, the authors detail the construction of a 400 W prototype and give the experimental outcomes, confirming the design’s viability and efficiency.